Genotype x Environment Interaction for Seed Yield and its Component Traits in Lentil - Solanki, L S; Phogat, D S (Annals of Arid Zone, 2016)
Thirty genetically' diverse genotypes of lentil (Lens cll/inaris Medik.) were evaluated for genotype x environment (G x E) interaction for seed yield and its component traits during three consecutive years from 1997-98 to 1999-2000 at CCS Haryana Agricultural University, I-1isar.Both linear mid non-linear components of G x E interactions were found important for the expression of grain yield and related traits. Ten genotypes were found' to be high yielders and stable for all the environments, whereas four and five genotypes were observed to be high yielding and stable for better and poor environments, respectively. Stability of genotypes with respect to grain yield plofl in all the environments Was imparted by the stability of different yield contributing traits.